Corporate Social Responsibility and Intellectual Capital and Their Influence on Annual Report Readability: A Literature Review - Novianri, Valentina Rani; Sarumpaet, Susi; Syaipudin, Usep (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the relationship between Corporate Social Responsibility (CSR) performance, Intellectual Capital, and the readability of annual reports as a key communication tool between companies and stakeholders. This research uses a qualitative literature review approach by analyzing several previous studies related to this topic. The results of the analysis show that companies that are actively involved in CSR practices and have strong Intellectual Capital tend to present annual reports with a higher level of readability. This optimal readability has a positive impact on the understanding of various stakeholders, including investors and creditors, which in turn can support better decision-making. The implication is that companies can utilize CSR practices and Intellectual Capital development as a strategy to increase the readability of their annual reports. Therefore, increasing transparency, readability and clear disclosure of information in annual reports can contribute positively to a company's reputation and support long-term business growth. Recommendations for companies involve paying attention to the regulatory and disclosure reform initiatives that regulators have implemented to ensure disclosure is effective and affordable for all stakeholders